The composition of Genesis 37: incoherence and meaning in the exposition of the Joseph story - Genung, Matthew C. (Forschungen zum Alten Testament / 2, 2017)
Cover -- Foreword -- Preface -- Table of Contents -- List of Figures -- Abbreviations & Symbols -- Chapter 1: History of Research -- 1. Documentary Hypothesis -- 1.1 Karl-David Ilgen -- 1.2 Hermann Hupfeld -- 1.3 Julius Wellhausen -- 1.4 Joel Baden -- 2. Form Criticism -- 2.1 Hermann Gunkel -- 2.2 Hugo Greßmann -- 2.3 Gerhard von Rad -- 3. Tradition Criticism -- 4. Unity -- 4.1 Wilhelm Rudolph -- 4.2 George Coats -- 4.3 Claus Westermann -- 5. Fortschreibung - Hypotheses of redactional updating -- 5.1 Donald Redford -- 5.2 Hans-Christoph Schmitt -- 5.3 Peter Weimar -- 6. Synchronic Readings -- 6.1 Jan Peter Fokkelman -- 6.2 James Ackerman -- 6.3 Edward Greenstein -- 6.4 Anthony Campbell and Mark O'Brien -- 7. Elements of Incoherence in the Text - A Summary -- 7.1 Tensions arising from reading the Joseph Story in the Pentateuch -- 7.2 Tensions arising from reading Genesis 37 in the Joseph Story -- 7.3 Problems internal to Genesis 37 -- 8. Analysis -- 9. Status Quaestionis -- Chapter 2: Gen 37,18-30 and the Sale of Joseph -- 1. Statement of Problem -- 2. Proposed Synchronic Solutions -- 2.1 The Midianites are Ishmaelites -- 2.2 The Midianites sold Joseph to the Ishmaelites -- 3. Proposed Diachronic Solutions -- 3.1 The text is a composition from two sources -- 3.1.1 Hermann Gunkel's proposal -- 3.1.2 Joel Baden's proposal -- 3.1.3 The hermeneutic of A. F. Campbell and M. A. O'Brien -- 3.1.4 Provisional conclusion -- 3.1.5 Analysis of ostensible doublets in Gen 37,18-30 -- 3.2 The section contains a short redactional addition -- 3.2.1 Erhard Blum's proposal -- 3.2.2 Analysis of Blum's proposal -- 3.2.3 Provisional conclusion -- 3.3 The text contains an original version and a redactional layer -- 3.3.1 'Judah' base text with 'Reuben' expansion -- 3.3.2 'Reuben' base text with 'Judah' expansion -- 3.3.3 Provisional conclusion.